“In God We Trust” – A Legal History of the Emergence, Development and Influence of the Sexual Abuse Scandal within America’s Catholic Clergy - Jones, Elanor (2011)
The position of the Catholic Church within American civic culture has been irreparably altered by the emergence of widespread allegations of sexual abuse by Church officials between 1960 and 2005. This thesis examines the role of the law in the development of this scandal: how the legal position of the Church contributed to its creation, how civil litigation produced its exposure and how the secular legal system answered its demand for legal reform. In doing so, it will argue that, contrary to traditional legal assumptions, private lawsuits were the defining influence on the public crisis that confronted the Church. The allegations of abuse and their expression through this litigation debunked the regulatory autonomy of the Church and thereby caused a powerful rupture in the historical relationship of Church and State